1996
DOI: 10.1088/0953-2048/9/4a/023
|View full text |Cite
|
Sign up to set email alerts
|

Single-layer and integrated YBCO gradiometer coupled SQUIDs

Abstract: For many SQUID applications such as biomagnetism or non-destructive evaluation it is convenient or even necessary to work without the restrictions of a magnetically shielded room. This contribution deals with two sensors appropriate for this purpose.In the first concept we present a flip chip arrangement of a single-layer flux transformer and a single-layer SQUID, taking advantage of a simple technology. The SQUID was prepared on a 15 × 15 mm 2 SrTiO 3 24 • bicrystal and located in the common line of two-paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Peiselt et al [12], after investigating different coupling loops, achieved an overall optimized sensitivity of 12 fT cm −1 Hz −1/2 (white) and 310 fT cm −1 Hz −1/2 at 1 Hz in an unshielded environment. Other flip-chip gradiometer designs have been fabricated by Dantsker et al [13] and Bär et al [14] who demonstrated a gradient sensitivity of 20 fT cm −1 Hz −1/2 at 1 kHz (unshielded). However, this flip-chip design has some advantages over conventional flipchip arrangements (generally inductive coupling to a small dc washer SQUID).…”
Section: Planar Sensor Design and Optimizationmentioning
confidence: 99%
“…Peiselt et al [12], after investigating different coupling loops, achieved an overall optimized sensitivity of 12 fT cm −1 Hz −1/2 (white) and 310 fT cm −1 Hz −1/2 at 1 Hz in an unshielded environment. Other flip-chip gradiometer designs have been fabricated by Dantsker et al [13] and Bär et al [14] who demonstrated a gradient sensitivity of 20 fT cm −1 Hz −1/2 at 1 kHz (unshielded). However, this flip-chip design has some advantages over conventional flipchip arrangements (generally inductive coupling to a small dc washer SQUID).…”
Section: Planar Sensor Design and Optimizationmentioning
confidence: 99%
“…Many planar-type high-T c SQUID gradiometers have been previously reported [4][5][6][7][8][9][10][11][12][13][14][15][16]. The gradient field noise and baseline lengths, which are given in these references, have been collected (figure 2).…”
Section: Gradient-field-noise Limit Of Gradiometersmentioning
confidence: 99%
“…Many planar-type high-T c SQUID gradiometers have recently been developed [4][5][6][7][8][9][10][11][12][13][14][15][16], because they can be operated in liquid nitrogen without adjustments of gradiometric balance. However, their feasibility for detecting P-waves has not been sufficiently evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…An incoupling antenna with large area on a single crystalline substrate inductively coupled to a read-out sensor on a bicrystal substrate in available size (flip-chip gradiometer or magnetometer) [2] offers a solution. Different groups already realized this concept [3][4][5]. In this paper we are going to discuss a new layout version following this concept.…”
Section: Introductionmentioning
confidence: 99%